2018
DOI: 10.1088/1367-2630/aadf9f
|View full text |Cite
|
Sign up to set email alerts
|

A polynomial eigenvalue approach for multiplex networks

Abstract: We explore the block nature of the matrix representation of multiplex networks, introducing a new formalism to deal with its spectral properties as a function of the inter-layer coupling parameter. This approach allows us to derive interesting results based on an interpretation of the traditional eigenvalue problem. Specifically, our formalism is based on the reduction of the dimensionality of a matrix of interest but increasing the power of the characteristic polynomial, i.e, a polynomial eigenvalue problem. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A particularly relevant development is the extension of contagion processes to multilayer networks, which in turn paved the way to combinatorial higher-order models. Indeed, multilayer's structural [13][14][15][16][17] and spreading and diffusion properties [5,13,14,18] have a new and richer phenomenology. Nevertheless, as recently argued in [19], real data is revealing that pairwise relationships -the fundamental interaction units of networks -do not capture complex dependencies.…”
mentioning
confidence: 99%
“…A particularly relevant development is the extension of contagion processes to multilayer networks, which in turn paved the way to combinatorial higher-order models. Indeed, multilayer's structural [13][14][15][16][17] and spreading and diffusion properties [5,13,14,18] have a new and richer phenomenology. Nevertheless, as recently argued in [19], real data is revealing that pairwise relationships -the fundamental interaction units of networks -do not capture complex dependencies.…”
mentioning
confidence: 99%
“…Interestingly [15], showed that multiplex networks can have super-diffusive behavior, meaning that their time scale to relax to the steady state is smaller than that of any layer taken in isolation. Since then, the spectral properties of multiplex networks have been widely investigated [19][20][21][22][23], and the formalism has been extended to describe more complex phenomena, such as reaction-diffusion [24][25][26] and synchronization processes [27]. Nevertheless, while it was suggested that low correlation in the structure of the layers can enhance diffusion in a multiplex [28], a rigorous theory for the emergence of super-diffusion is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…t α = t, ∀α. In this scenario, we can obtain the exact transition point, t * , by reformulating the eigenvalue problem for the supra-Laplacian in terms of a polynomial eigenvalue problem [26]. In general, a polynomial eigenvalue problem is formulated as an equation of the form…”
Section: Continuous Layers Degradationmentioning
confidence: 99%